Structure-function relationships in the sodium chloride cotransporter - Moreno, Erika; Pacheco-Alvarez, Diana; Chávez-Canales, María; Elizalde, Stephanie; Leyva-Ríos, Karla; Gamba, Gerardo (Frontiers in Physiology, 2023)
The thiazide sensitive Na+:Cl- cotransporter (NCC) is the principal via for salt reabsorption in the distal convoluted tubule (DCT) in mammals and plays a fundamental role in managing blood pressure. The cotransporter is targeted by thiazide diuretics. NCC was the first member of the SLC12 family to be identified at a molecular level. It was cloned from the urinary bladder of the Pseudopleuronectes americanus (winter flounder) thirty years ago. The structural topology, kinetic and pharmacology properties of NCC have been extensively studied, determining that the transmembrane domain (TM) coordinates ion and thiazide binding. Functional and mutational studies have discovered residues involved in the phosphorylation and glycosylation of NCC, particularly on the N-terminal domain, as well as the extracellular loop connected to TM7-8 (EL7-8). In the last decade, single-particle cryogenic electron microscopy (cryo-EM) has permitted the visualization of structures at high atomic resolution for six members of the SLC12 family (NCC, NKCC1, KCC1-KCC4). Cryo-EM insights of NCC confirm an inverted conformation of the TM1-5 and TM6-10 regions, a characteristic also found in the amino acid-polyamine-organocation (APC) superfamily, in which TM1 and TM6 clearly coordinate ion binding. The high-resolution structure also displays two glycosylation sites (N-406 and N-426) in EL7-8 that are essential for NCC expression and function. In this review, we briefly describe the studies related to the structure-function relationship of NCC, beginning with the first biochemical/functional studies up to the recent cryo-EM structure obtained, to acquire an overall view enriched with the structural and functional aspects of the cotransporter.